2021
DOI: 10.1146/annurev-biodatasci-021621-122219
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Allele-Specific Expression

Abstract: Diploidy has profound implications for population genetics and susceptibility to genetic diseases. Although two copies are present for most genes in the human genome, they are not necessarily both active or active at the same level in a given individual. Genomic imprinting, resulting in exclusive or biased expression in favor of the allele of paternal or maternal origin, is now believed to affect hundreds of human genes. A far greater number of genes display unequal expression of gene copies due to cis-acting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 112 publications
0
33
0
Order By: Relevance
“…We hypothesize that the intronic variants alter gene expression in cis, detectable as allelic imbalance in PKLR expression. 14,15 Screening of PKLR revealed a synonymous variant (R596R, rs1052176) in exon 11 (Figure 1A); its prevalence in almost 50% of NIH SCD patients, makes it a highly suitable marker for differentiating expression of the 2 alleles. We examined the pairwise LD between PKLR variants and found that all the six intron 2 variants were in tight linkage disequilibrium (LD), while R596R belongs to another LD block (Supplemental Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that the intronic variants alter gene expression in cis, detectable as allelic imbalance in PKLR expression. 14,15 Screening of PKLR revealed a synonymous variant (R596R, rs1052176) in exon 11 (Figure 1A); its prevalence in almost 50% of NIH SCD patients, makes it a highly suitable marker for differentiating expression of the 2 alleles. We examined the pairwise LD between PKLR variants and found that all the six intron 2 variants were in tight linkage disequilibrium (LD), while R596R belongs to another LD block (Supplemental Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…22 Allelic variation in human gene expression is common and population-based studies provide increasing evidence that non-coding variants influence trait variance and quite likely, response to pharmacotherapy. 15,22 Studies have suggested that PK deficiency provides protection from malaria infection, accounting for the high frequency of PKLR variants in sub-Saharan African populations. 23,24 Indeed, the PKLR intron 2 variants described here have a minor allele frequency of 14-15% in African populations in 1000 Genomes Project, and almost absent in non-African populations.…”
Section: Resultsmentioning
confidence: 99%
“…It is plausible that differential expression can contribute to disease in monoallelic IRIDA when it favors the affected TMPRSS6 allele and reduces the expression of the functional allele. Generally, this provides an explanation for the clinical presentation of monoallelic-affected IRIDA patients to have a greater effect on the phenotype in these individuals [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, any other clinical factor that's correlated with the cell fraction could be the causal mediator (for example -tumor stage, site of sampling and BMI), which could be further investigated by incorporating additional relevant interaction terms. Sixth, AI can be the consequence of many mechanisms such as nonsense-mediated decay, imprinting, post-translational effects and alternative splicing [67]. By assuming consistent AI/QTL effects in DeCAF, our approach may lose power when these deviating effects are present.…”
Section: Discussionmentioning
confidence: 99%